2004
DOI: 10.1002/dmrr.473
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebral infarction in patients with type 2 diabetic nephropathy. Effects of antiplatelet drug dilazep dihydrochloride

Abstract: These data suggest that diabetic renal dysfunction increases the risk of silent cerebral infarction and that dilazep dihydrochloride prevents its onset in early type 2 diabetic nephropathy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…This differs from the results obtained by Nakamura and his colleague [16] who found that 20% had silent cerebral infarction. This difference could be due to differences in study design, sample size or the degree of disease progression before the MRI brain scan was conducted.…”
Section: Discussioncontrasting
confidence: 98%
“…This differs from the results obtained by Nakamura and his colleague [16] who found that 20% had silent cerebral infarction. This difference could be due to differences in study design, sample size or the degree of disease progression before the MRI brain scan was conducted.…”
Section: Discussioncontrasting
confidence: 98%
“…None of the patients had been given antihypertensive drugs, including angiotensin-converting enzyme inhibitor or angiotensin receptor blocker, or antiplatelet drugs, i.e. drugs reported to be renoprotective [9,10]. There was no malignancy, heart disease, cerebrovascular disease, liver disease, or collagen disease, according to a physical examination and urine and blood test results and radiography, electrocardiography, ultrasound cardiography, or X-ray computed tomography data.…”
Section: Methodsmentioning
confidence: 98%
“…However, since only CT was used in this study for the detection of SBI, the validity of its findings is doubtful as CT is insensitive for detection of small brain infarcts. In two small open-labeled randomized controlled studies using antithrombotic agents (cilostazol, n = 89; dilazep hydrochloride, n = 30) among diabetic patients, the incidence of SBI was significantly lower in the active group than in the placebo group over 2–3 years [25,26]. …”
Section: Discussionmentioning
confidence: 99%